Analysis Of Technological Pedagogical Content Knowledge (TPACK) of Elementary School Teacher Education Students In Developing Merdeka Curriculum Lesson Plans: Analysis Of Technological Pedagogical Content Knowledge (TPACK) Of Elementary School Teacher Education Students In Developing Merdeka Curriculum Lesson Plans - ida Putriani (Universitas Islam Balitar, 2023)
The change in the curriculum demands that students as prospective teachers must be able to master all components of the curriculum. One of the mandatory skills to possess is the ability to develop teaching materials. Initial observation indicates that students still have difficulty understanding the content and technology integration in the independent curriculum, even though TPACK is the main capital that teachers must possess in the 21st century. This research aims to describe the TPACK abilities of students in developing teaching materials for the independent curriculum. This study is qualitative research. The subjects of this study are 21 fourth-semester PGSD UNISBA students. Data collection is conducted through observation, interviews, field notes, and documentation. The results of the study show that the TPACK abilities of students in developing independent curriculum teaching materials are: TK component with a good percentage of 81%, CK component 76%, PK component 71%, PCK component 57%, TPK component 67%, and TCK component 57%. The ability of students to develop teaching materials for the independent curriculum shows that their PCK and TCK abilities are constrained by their low understanding of the process and principles of the independent curriculum